The Effect of the Adapted Physical Education Course on the Attitudes of the University Students towards the Education of Individuals with Disabilities - Murat Ergin (Türk Spor ve Egzersiz Dergisi)
The aim of this study was to determine the effect of an undergraduate Sports for the Disabled course on the attitudes of Sports Science students towards the education of individuals with disabilities. The study group consisted of 119 Sports Sciences Faculty Coaching Education Department students studying at Aksaray University. The data were collected with the "Personal Information Form" and the "Attitude toward Disabled Persons Scales" (ATDP). The course of Sports for the Disabled was given to the participants theoretically for 14 weeks and 60 minutes a week. After the descriptive statistics of the study data were determined, the normality of the data was tested with the Shapiro-Wilk test and the comparison of pre-test and post-test scores was conducted with Paired Samples t-Test. The margin of error for all analyzes was taken as p lt;0.01. It was concluded that the Sports for the Disabled course positively affected the attitudes of the Faculty of Sports Sciences students towards the education of individuals with disabilities.